A comparative study on the user comfort perception of the post-independence and post-millennium era public secondary school classroom in Malaysia - Bu, Raymond Kiat Meng; Zunaibi Abdullah,; Nazli Che Din, (Penerbit Universiti Kebangsaan Malaysia, 2021)
The physicality of the classroom has significant influence on the comfort on both teacher and students which associated with the school learning environment. With the current trends moving towards improving the education system and programs in Malaysia, many standards in terms of the comfort level in the classroom of the public school were not taken into consideration as part of the reform measures. This study aims to investigate and analyse how public secondary school classroom design built during Post-Independence and Post-Millennium era affects the perception of student comfort level. A comparative study between public secondary school built in Post-Independence and Post-Millennium Era to uncover the relation of classroom design on the user comfort level, where one case study from each school from respective era is selected for on-site observations and survey questionnaire method is carried out. The fundamental parameters of comfort level are being assessed which is (a) thermal comfort, (b) visual comfort and (c) air quality through case study observation and questionnaires set up with the students on their perception of comfort level being in the classroom. The results were then analysed by carrying out statistical analysis, and evidence indicates that the conditions of the classroom has significant impact on the occupant’s comfort level. Furthermore, the classroom in school built during the post-independence era and post-millennium has different architecture and planning aspect which has an impact on the conduciveness of the classroom and contributes to certain comfort level factor satisfaction. This research and findings will aid to provide a guide for the development of future public secondary school design that promotes user comfort in the classroom which will then create an effective learning space.